Changing the lifestyles of young adults. Issue 3 (13th July 2015) - Giles, Emma Louise; Brennan, Mary
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the costs and benefits that young adults perceive to be associated with adopting healthier food, alcohol and physical activity behaviours. Social marketing is used to identify and change behaviours within a segmented audience. The approach uses theoretical insights, and an appreciation of an individual's environment, and a suite of methods to understand and suggest approaches to change behaviours. Design/methodology/approach – Focus groups were conducted between April and August 2007 with a sample of 54 young adults aged 19-24 years, from the North East of England. Qualitative thematic analysis was undertaken using Nvivo software. Findings – Young adults recognise future health benefits that they could gain from following healthier lifestyle behaviours; however, at their present age, their focus is on benefits such as weight regulation and improving one's appearance. External competitive forces act against these benefits and result in time and effort costs associated with accepting the proposition of healthier lifestyle behaviours. Originality/value – This paper adds to limited research which has been conducted at the time of "emerging adulthood", the period of 18-25 years of age. This is despite this being an opportunistic moment in young adult's lives to encourage them to adopt healthier lifestyle behaviours. Given these results, health messages may need to be reframed to better account for the benefits and costs that young adults associate with healthier lifestyles.